Interpretasi Ayat Iddah Bagi Wanita Menopause, Amenorea, Dan Hamil Dengan Pendekatan Medis - Musyafaâ€™ah, Nur Lailatul (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
Abstract: This article discusses the verse of the Quran concerning iddah (waiting period after divorce or death of husband). The concerned verse is QS. 65:4. It stipulates iddah for menopause women, amenorrhea women, and pregnant women. Muslim jurists agree that waiting period for menopause and amenorrhea women is three lunar months, whereas pregnant women must wait until labor. Medical examination shows several advantages for waiting period. Firstly, the word â€œin irtabtumâ€ (when you have doubt) in the verse for menopause women, that women before menopause tend to get their menstrual period irregularly which in medical perspective a menopause women are those who have not get their menstrual period in a full year. Secondly, the attribute to women who not yet get menstruation and not yet pregnant, because there are two types of amenorrhea; primary and secondary. Primary amenorrhea for those who never get menstruation whereas secondary amenorrhea is caused by pregnancy or other causes. Thirdly, the attribute in the verse of iddah for pregnant women with â€œan yadhaâ€™na hamlahunnaâ€ not with â€œan yalidnaâ€ means that pregnancy take place when ovum was fertilized by sperm. Thus, when there is no pregnancy, either because of miscarriage or labor, the iddah concludes. Key words: iddah, Quranic interpretation, medical knowledge